ANALISIS PENGARUH DISIPLIN KERJA, KERJA SAMA TIM DAN PENGAWASAN TERHADAP KEPUASAN KERJA PADA PT INSAN SUMBER MANDIRI - Siti Zahra Pohan; Aswan Waruwu (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
. The research analysis aims to determine work discipline, teamwork and supervision of employee performance. The data analysis technique used is an associative research method with the help of the SPSS version 19 program. This research uses multiple linear regression analysis. The sample in this study was 43 respondents. Primary data collection uses a questionnaire. The research results show that teamwork has a positive and significant effect on job satisfaction. This can be seen from the hypothesis test with a tcount value of 2.310 > ttable of 2.02 with a significant value of 0.026 < 0.05, so hypothesis H2 is accepted and H0 is rejected. Teamwork has a positive and significant effect on job satisfaction, this can be seen from the hypothesis test with a tcount value of 2.310 > ttable of 2.02 with a significant value of 0.026 <0.05, then the hypothesis H2 is accepted and H0 is rejected. Supervision has a partially positive and significant effect regarding job satisfaction, this can be seen from the hypothesis test with a t value of 2.310 > t table of 2.02 with a significant value of 0.026 < 0.05, so the hypothesis H2 is accepted and H0 is rejected. Work discipline, teamwork and supervision simultaneously have a positive and significant effect on employee performance. This can be seen from the calculated F value of 89.078 which is greater than 2.84 and the significant value of 0.000 is smaller than 0.05 so it can be concluded that the H4 hypothesis is accepted and the H0 hypothesis is rejected.